2015
DOI: 10.1016/j.neuroscience.2014.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Early-life exposure to the SSRI paroxetine exacerbates depression-like behavior in anxiety/depression-prone rats

Abstract: Selective serotonin reuptake inhibitor (SSRI) antidepressants are the mainstay treatment for the 10–20% of pregnant and postpartum women who suffer major depression, but the effects of SSRIs on their children’s developing brain and later emotional health are poorly understood. SSRI use during pregnancy can elicit antidepressant withdrawal in newborns and increase toddlers’ anxiety and social avoidance. In rodents, perinatal SSRI exposure increases adult depression- and anxiety-like behavior, although certain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 157 publications
(247 reference statements)
5
91
0
Order By: Relevance
“…Our group and others previously reported HR/LR differences in behavioral despair [14], aggression [15], and anxiety-like behavior [13]. These differences suggested that HR rats display a proactive coping style while LRs display a reactive coping style.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Our group and others previously reported HR/LR differences in behavioral despair [14], aggression [15], and anxiety-like behavior [13]. These differences suggested that HR rats display a proactive coping style while LRs display a reactive coping style.…”
Section: Discussionmentioning
confidence: 52%
“…Rats bred for high response to novelty (High Responders, HRs) vigorously explore new environments compared to rats bred for low novelty response (Low Responders, LRs). Selective breeding produced rats with differences in anxiety/depression-like behavior, with LR rats displaying high and HR rats displaying low anxiety/depression-like behavior as measured by the forced swim test (FST) [14], resident-intruder test [15], and elevated plus maze [13]. These behavioral differences suggest that HRs display proactive coping across several tests while LRs display reactive coping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA samples from the HR and LR P7/P14/P21 hippocampus, amygdala, and prefrontal cortex (n=5 samples/group) were shipped on dry ice for genome-wide expression profiling using NimbleGen Rat Gene Expression 12×135 Arrays (26,419 target genes, 5 probes/targets; Arraystar, Rockville, MD) as previously described (Glover et al, 2015). Briefly, RNA quality and quantity were assessed with Nanodrop ND-1000 (Thermo Scientific, Wilmington, DE) and the RNA integrity was evaluated through denaturing agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…In rodents, exposure to SSRIs in the prenatal and/or early neonatal period disrupts dendritic organization and formation of thalamocortical afferents to the somatosensory cortex and results in aberrant axonal morphology, abnormal raphe circuitry, and altered cortical function (Lee, 2009; Liao and Lee, 2011; Simpson et al, 2011; Xu et al, 2004). These changes are accompanied by behavioral disturbances including decreased exploratory behavior and increased emotional reactivity, altered social behavior, and impaired motor performance (Borue et al, 2007; Glover et al, 2015; Xu et al, 2004). …”
Section: Introductionmentioning
confidence: 99%